دور تكنولوجيا المعلومات في تدعيم وتفعيل إدارة علاقات الزبائن - د.غالم, عبد الله; أ.قريشي, محمد (Recherches économiques et managériales, 2011)
تعتبر إدارة علاقات الزبائن من أكبر مجالات الأعمال نموا في عصرنا الحالي، وأكثرها سرعة في التعامل مع التقنيات الحديثة؛ إذ نجد أن الكثير من المؤسسات تنفق على صفحاتها عبر الانترنت الملايين من الدولارات لتطبيقات وممارسات إدارة علاقات الزبائن، وذلك راجع لكون أن هذه المؤسسات تدرك جيدا ضرورة فهم احتياجات زبائنها والحصول على رضائهم من أجل تحقيق ميزة تنافسية. وعليه لا بد أن تنظر المؤسسات إلى زبائنها باعتبارهم مشترين للعلاقات الطيبة المستمرة بدلا من مشترين لمنتجاتها. وعلى العموم فان التطورات الكبيرة الحاصلة في مجال تكنولوجيا المعلومات جعلت إمكانية التعامل مع المعلومات المتنوعة والمعقدة المتعلقة بالزبائن، في صورة تطبيقات برمجية لإدارة علاقات الزبائن بالمؤسسة لتحقيق فهم أكثر عمقا للزبائن ولاحتياجاتهم ورغباتهم.      ونهدف من خلال هذه الورقة البحثية إلى التعرف على الدور الذي تلعبه تكنولوجيا المعلومات في تدعيم وتفعيل إدارة علاقات الزبائن. Abstract    Customer Relationship Management knowing the largest growth among all other business areas recently, and the fastest in dealing with modern technologies. There for many enterprises spend millions of dollars for web-based applications to practice customers relationship management on the internet. this is mainly due to the fact that enterprises recognize their needs to comprehend customer’s needs, and to obtain their satisfaction in order to achieve competitive advantage. Hence, enterprises should consider their costumers as good relationship buyers instead of their products buyers.    In General, the major developments in the information technology area has made possible the dealing with the diverse and complex nature of costumer’s related information, in form of software and application to manage the relationships between costumers and enterprises to achieve deeper comprehension of costumers and their desires and needs.    In This paper, we present The Role of Information Technology On The Enhancement of Customer  Relationship Management  Effectiveness.